Anti-aging EVA supercritical foaming sole and preparation method thereof
By using polystyrene-acrylate-acrylamide block copolymer as elastomer in EVA foamed sole material, combined with RAFT polymerization technology and blending modification method, the problem of taking into account the aging resistance and high rebound properties of the existing materials is solved, and the high aging resistance and high rebound properties of the materials are achieved.
Patent Information
- Application Number
- CN202510034630.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-01-09
- Publication Date
- 2025-03-21
AI Technical Summary
The existing EVA foamed sole materials are difficult to balance between aging resistance and high rebound properties, and are prone to yellowing and elastic deterioration when exposed to sunlight for a long time.
A block copolymer with polystyrene as the hard segment and acrylate-acrylamide random copolymer as the soft segment is used as the elastomer. The molecular weight and structure are controlled through RAFT polymerization technology, and blended and modified with SEBS, fillers, wear-resistant agents and crosslinking agents to prepare an aging-resistant EVA supercritical foam sole.
It improves the material's aging resistance and high rebound performance, extends its service life, and is especially suitable for EVA foamed soles.
Smart Images

Figure CN119661929A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of plastics, in particular to an aging-resistant EVA supercritical foaming sole and a preparation method thereof. Background Art
[0002] With the rapid development of economy and technology, my country has become the largest country in shoe manufacturing and production, with an annual production capacity of over 3 billion pairs of shoes. A pair of sports shoes is mainly divided into three parts: upper, midsole, and outsole. The midsole is the core component of a pair of sports shoes. Its function is to provide stability and rebound performance for the wearer and absorb the impact generated during exercise. In 1974, Brooks first used a revolutionary polymer material-EVA (ethylene-vinyl acetate copolymer). Due to its light weight and obvious shock absorption effect, it quickly replaced rubber and became the most widely used midsole material. However, the single EVA substrate has poor flexural resistance, elasticity and wear resistance, which also limits its use scenarios to a certain extent. In recent years, various new polymer elastomers have sprung up like mushrooms after rain, which also makes EVA foamed shoe materials have new properties such as high rebound, high wear resistance, low density, and low compression deformation. Therefore, the blended modified foaming material based on EVA has become the mainstream of the industry.
[0003] As a lightweight and elastic polymer material, the elastomer of foam material has the excellent properties of high elasticity, aging resistance, wear resistance and other excellent properties of traditional cross-linked vulcanized rubber, and at the same time has the characteristics of convenient processing of ordinary plastics. It has received extensive attention and application in the production of foam materials in recent years. Among them, common elastomers include olefin block copolymers (OBC), thermoplastic polyurethanes (TPU), hydrogenated styrene-butadiene block copolymers (SEBS), etc. Through melt blending modification, the elasticity, wear resistance and other properties of EVA composite materials can be improved. However, the mechanical properties of OBC are greatly affected by temperature, and the high temperature and ultraviolet resistance of TPU are relatively weak. It is easy to yellow and deteriorate elasticity when exposed to sunlight for a long time. The aging resistance of both is not good enough. Although SEBS has good aging resistance, it has relatively strong rigidity and insufficient resilience. Therefore, it is still necessary to select an elastomer with both resilience and aging resistance for use in EVA foam sole materials. Summary of the invention
[0004] In order to overcome the deficiencies of the above-mentioned prior art, the present invention provides an aging-resistant EVA supercritical foaming sole and a preparation method and application thereof, so as to obtain an EVA supercritical foaming sole with high resilience and aging resistance.
[0005] The technical solution for achieving the purpose of the present invention is as follows: An aging-resistant EVA supercritical foaming sole comprises the following components by weight: 10-80 parts of EVA, 10-30 parts of elastomer, 0-20 parts of SEBS, 0-20 parts of filler, 0-10 parts of wear-resistant agent, and 0.5-3 parts of cross-linking agent; the elastomer is a block copolymer with polystyrene as a hard segment and acrylate-acrylamide random copolymer as a soft segment, and the general structural formula of the elastomer is shown in Formula 1:
[0006] Formula 1 Wherein, R is at least one of ethyl, propyl, butyl and isooctyl.
[0007] Specifically, the content of styrene in the elastomer is 10-30wt%, the content of acrylate is 50-80wt%, and the content of acrylamide is 5-20wt%; preferably, the content of styrene in the elastomer is 20-30wt%, the content of acrylate is 50-65wt%, and the content of acrylamide is 15-20wt%.
[0008] Specifically, the molecular weight of the elastomer is 90,000 to 1,000,000; preferably, the molecular weight of the elastomer is 200,000 to 500,000, and the molecular weight is the number average molecular weight measured by gel permeation chromatography (GPC).
[0009] Specifically, the preparation method of the elastomer is: firstly, styrene, a chain transfer agent and an initiator are subjected to a reversible addition-fragmentation chain transfer (RAFT) polymerization reaction to obtain polymerized styrene, and then acrylate, acrylamide and polymerized styrene are copolymerized under the action of the initiator to obtain the elastomer.
[0010] RAFT polymerization is a technology that controls free radical polymerization. By using special chain transfer agents, it is possible to control chain growth and termination during the polymerization process, thereby achieving precise control over the molecular weight and structure of the polymer.
[0011] Specifically, the RAFT polymerization reaction temperature is 120-140° C., and the reaction time is 4-8 hours; the copolymerization reaction temperature is 70-90° C., and the reaction time is 20-60 minutes; the initiator is azobisisobutyronitrile; and the chain transfer agent is 2,2'-[thiocarbonyl(sulfur)]bis[2-methylpropionic acid].
[0012] Preferably, the aging-resistant EVA supercritical foaming sole comprises the following components by weight: 40-80 parts of EVA, 20-30 parts of elastomer, 10-20 parts of SEBS, 10-20 parts of filler, 5-10 parts of wear-resistant agent, and 1-2 parts of cross-linking agent.
[0013] Preferably, the filler is at least one of calcium carbonate, talc, barium sulfate or titanium dioxide.
[0014] Preferably, the anti-wear agent is polysiloxane, and the molecular weight of the polysiloxane is 10,000 to 500,000.
[0015] Preferably, the crosslinking agent is at least one of dicumyl peroxide, di-tert-butyl peroxycumene, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane and tert-amyl peroxy(2-ethylhexyl)carbonate.
[0016] Preferably, the vinyl acetate (VA) content of the EVA is 10 wt % to 60 wt %.
[0017] Preferably, the aging-resistant EVA supercritical foaming sole further includes 0.1 to 2 parts of an antioxidant, and the antioxidant is at least one of antioxidant 1010 or antioxidant 168.
[0018] The present invention also protects a method for preparing the aging-resistant EVA supercritical foaming sole, which comprises the following steps: S1. Premixing EVA, elastomer, SEBS, crosslinking agent, filler and wear agent in a high mixer to obtain an EVA composition; S2. The composition obtained in S1 is granulated, and then injection molded at an injection temperature of 80 to 130°C and a mold temperature of 150 to 200°C, and the pressure is maintained for 200 to 800s to form a shoe embryo; S3. Place the shoe base obtained in step 2 into N 2 The foaming was carried out in a supercritical reactor, and the N 2 The pressure is 10-20 MPa, the foaming temperature is 100-200°C, the heat and pressure holding time is 0.5-4 hours, then the pressure is released, the product is taken out and cooled to room temperature to obtain a finished shoe sole.
[0019] On the other hand, the present invention also protects the application of the aging-resistant EVA supercritical foaming sole, specifically: a sports shoe, comprising the aging-resistant EVA supercritical foaming sole.
[0020] Beneficial Effects The invention provides an aging-resistant EVA supercritical foaming sole and a preparation method and application thereof. The invention adopts a block copolymer elastomer with polystyrene as a hard segment and acrylate-acrylamide random copolymer as a soft segment to be blended and modified in an EVA material, wherein the polystyrene hard segment in the elastomer is in a crystalline state at a use temperature, provides higher strength and modulus, enables the elastomer to withstand a certain external force without being easily deformed, and reduces the erosion of the soft segment by external environmental factors such as ultraviolet rays, oxygen, moisture, etc., thereby improving the aging resistance of the elastomer; the acrylate-acrylamide random copolymer soft segment is in a crystalline state at a use temperature, provides higher strength and modulus, enables the elastomer to withstand a certain external force without being easily deformed, and reduces the erosion of the soft segment by external environmental factors such as ultraviolet rays, oxygen, moisture, etc., thereby improving the aging resistance of the elastomer; It is in an elastic state at the operating temperature, which gives the material good flexibility and elasticity. The C=O in the acrylate can form a hydrogen bond with the amide group of acrylamide. When subjected to external force, the hydrogen bond can be reversibly broken, allowing the molecular chain to slide relatively, thereby allowing the material to undergo a large deformation. When the external force is removed, the molecular chain tends to return to its initial state, and the broken hydrogen bonds can be reformed, thereby improving the elongation at break and the elastic recovery ability of the elastomer, and the service life of the material is further improved. It is particularly suitable for use in EVA foam soles to prepare sole materials with high resilience and aging resistance. BRIEF DESCRIPTION OF THE DRAWINGS
[0021] Figure 1 Schematic diagram of the synthesis route of the elastomer; Figure 2 is the H NMR spectrum of polymerized styrene 1; Figure 3 is the H-NMR spectrum of elastomer 1. DETAILED DESCRIPTION
[0022] The following will be combined with the embodiments of the present invention to clearly and completely describe the technical solutions in the embodiments of the present invention. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0023] In the examples, the experimental methods used are conventional methods unless otherwise specified, and the materials, reagents, etc. used are all commercially available unless otherwise specified.
[0024] The raw materials used in the embodiments and comparative examples are described as follows: EVA: vinyl acetate content 18%, brand 7350M, Formosa Plastics Corporation; Filler: calcium carbonate, CC968, Guangxi Hezhou Kelong Powder Co., Ltd.; Wear-resistant agent: polysiloxane, 107 silicone rubber B, viscosity 10000 mPa.s (25°C), purchased from Jinan Longcheng Silicone Co., Ltd.; Antioxidant: a compound of antioxidant 1010 and antioxidant 168 in a mass ratio of 1:1, commercially available; SEBS: brand 1650, styrene content 30%, Kraton, USA; Cross-linking agent: dicumyl peroxide, 98%, purchased from Suzhou Senfeida Chemical Co., Ltd.; Styrene; 99.7%, purchased from Taiwan Styrene Industry Co., Ltd.; Acrylate 1: ethyl acrylate, 99%, purchased from Jiangsu Bosite Chemical Technology Co., Ltd.; Acrylate 2: butyl acrylate, 99%, purchased from Changzhou Xintong Chemical Co., Ltd.; Acrylate 3: 2-ethylhexyl acrylate, 99%, purchased from Jiangsu Bosite Chemical Technology Co., Ltd.; Acrylamide: 99%, purchased from Jiangsu Rayen Environmental Protection Technology Co., Ltd.; Initiator: azobisisobutyronitrile, 99%, purchased from Jinan Century Tongda Chemical Co., Ltd.; Chain transfer agent: 2,2'-[thiocarbonyl(thio)]bis[2-methylpropionic acid], 98%, purchased from Shanghai MacLean Biochemical Technology Co., Ltd.; Cyclohexane: 99.9%, Shanghai Aladdin Biochemical Technology Co., Ltd. Dimethylformamide: 99.9%, Shanghai Aladdin Biochemical Technology Co., Ltd. Elastomer 1: The designed molecular weight is 250000 g / mol, styrene accounts for 15wt%, butyl acrylate accounts for 70wt%, acrylamide accounts for 15wt%, and the preparation method is as follows: S1. In a nitrogen atmosphere, 144 mol parts of styrene and 0.025 mol parts of a chain transfer agent were added to a reactor. Nitrogen was first passed through the reactor for deoxygenation for 30 min at room temperature. Then, the reaction was heated to 130°C and stirred continuously. 0.0056 mol parts of an initiator were added dropwise to the reactor for bulk polymerization. After 6 hours of reaction, polymerized styrene 1 was obtained. Cyclohexane was added to the reaction system as a precipitant and stirred slowly to form a precipitate. The solvent and impurities were removed by vacuum devolatilization to obtain polymerized styrene. The synthesis route is as follows: Figure 1 shown.
[0025] The styrene degree of polymerization NS of polymerized styrene 1 was determined to be 361 by H NMR spectrum analysis, which is basically consistent with the designed degree of polymerization of 360. Figure 2 The specific steps are as follows: After the sample is purified and dried, 3 It is a nuclear magnetic reagent and is tested using BRUKER Avarice DMX 500. The degree of polymerization of polymerized styrene is determined by the two adjacent protons ( Figure 2 The integral value of the peak area of Hf in the styrene group is related to the proton on the side chain of the styrene group ( Figure 2 The peak area integral value of Ha in was compared to determine the value.
[0026] S2. Under nitrogen atmosphere, 546 mole parts of butyl acrylate, 211 mole parts of acrylamide and polymerized styrene 1 prepared in S1 were dissolved in dimethylformamide, firstly deoxygenated by nitrogen for 30 minutes, then heated to 80°C, 0.1 mole parts of initiator were added, stirred and reacted for 30 minutes to obtain elastomer 1, cyclohexane was added to the reaction system as a precipitant and slowly stirred to form a precipitate, filtered, washed with deionized water 3 times, and finally vacuum dried. The schematic diagram of the synthesis route of the elastomer is shown in Figure 1 shown.
[0027] The NMR hydrogen spectrum analysis determined that the degree of polymerization of styrene in elastomer 1 was 361, the degree of polymerization of butyl acrylate was 1358, the degree of polymerization of acrylamide was 521, the calculated molecular weight was 248,000, the number average molecular weight measured by gel permeation chromatography (GPC) was 234,900, and the molecular weight distribution coefficient was 1.37, which was basically consistent with the designed molecular weight. Figure 3 As shown, first, 3 × NS protons on the styrene side chain ( Figure 3 The peak area integration value of Hb at 6.85-7ppm in the butyl acrylate side chain is similar to the 2×NB protons ( Figure 3 The degree of polymerization of acrylamide is determined based on the signal in the range of 0.6ppm to 2.6ppm. Since NS and NB have been pre-determined by other characteristic signals, and the protons on the main chain of acrylamide ( Figure 3 The peaks of Hj and Hk in the styrene main chain appear in this ppm interval, so the peaks from the protons on the styrene main chain ( Figure 3 Hc and Hd in 3×NS), protons on the main chain and side chain of butyl acrylate ( Figure 3 After the peak area integration value of Hg, Hi and Hf in is equal to 10×NB), the obtained value corresponds to 3×Namide.
[0028] The detection instruments used for gel permeation chromatography are Waters 1525, Waters 2414 differential detector, Waters 2487 dual wavelength detector, Waters 717 autosampler, Waters Styragel Column (HR 5,4,3), the test range is: 4000000-500 g / mol, and the test temperature is constant at 30°C.
[0029] Elastomer 2: The designed molecular weight is 250000 g / mol, styrene accounts for 15wt%, ethyl acrylate accounts for 70wt%, and acrylamide accounts for 15wt%. The preparation method is the same as that of elastomer 1, except that 546 mole parts of butyl acrylate are replaced by 699 mole parts of ethyl acrylate; Elastomer 3: The designed molecular weight is 250000 g / mol, styrene accounts for 15wt%, isooctyl acrylate accounts for 70wt%, and acrylamide accounts for 15wt%. The preparation method is the same as that of elastomer 1, except that 546 mole parts of butyl acrylate are replaced by 379 mole parts of isooctyl acrylate; Elastomer 4: The designed molecular weight is 100000 g / mol, styrene accounts for 15wt%, butyl acrylate accounts for 70wt%, and acrylamide accounts for 15wt%. The preparation method is different from that of elastomer 1, except that the molar fraction of the chain transfer agent is 0.0625 molar fraction, the number average molecular weight measured by gel permeation chromatography (GPC) is 90760, and the molecular weight distribution coefficient is 1.28; Elastomer 5: The designed molecular weight is 500000 g / mol, styrene accounts for 15wt%, butyl acrylate accounts for 70wt%, and acrylamide accounts for 15wt%. The preparation method is different from that of elastomer 1, except that the molar fraction of the chain transfer agent is 0.0125 molar fraction, the number average molecular weight measured by gel permeation chromatography (GPC) is 485600, and the molecular weight distribution coefficient is 1.33; Elastomer 6: The designed molecular weight is 1000000 g / mol, styrene accounts for 15wt%, butyl acrylate accounts for 70wt%, and acrylamide accounts for 15wt%. The preparation method is different from that of elastomer 1, except that the molar fraction of the chain transfer agent is 0.00625 molar fraction; the reaction pressure is replaced from normal pressure to 300MPa high pressure reaction in a high pressure reactor, and the number average molecular weight measured by gel permeation chromatography (GPC) is 965230, and the molecular weight distribution coefficient is 1.42; Elastomer 7: The designed molecular weight is 250000 g / mol, the proportion of styrene is 30wt%, the proportion of butyl acrylate is 50wt%, and the proportion of acrylamide is 20wt%. The preparation method is different from that of elastomer 1, except that the molar proportion of styrene is 721, the molar proportion of butyl acrylate is 977, and the molar proportion of acrylamide is 690; Elastomer 8: The designed molecular weight is 250000 g / mol, the proportion of styrene is 20wt%, the proportion of butyl acrylate is 65wt%, and the proportion of acrylamide is 15wt%. The preparation method is different from that of elastomer 1, except that the molar proportion of styrene is 481 molar proportions, the molar proportion of butyl acrylate is 1270, and the molar proportion of acrylamide is 529; Elastomer 9: The designed molecular weight is 250000 g / mol, the proportion of styrene is 20wt%, the proportion of butyl acrylate is 75wt%, and the proportion of acrylamide is 5wt%. The preparation method is different from that of elastomer 1, except that the molar proportion of styrene is 481, the molar proportion of butyl acrylate is 1465, and the molar proportion of acrylamide is 176; Elastomer 10: The designed molecular weight is 250000 g / mol, the proportion of styrene is 30wt%, and the proportion of butyl acrylate is 70wt%. The preparation method is different from that of elastomer 1, except that the molar proportion of styrene is 721, and the molar proportion of butyl acrylate is 1367.
[0030] It should be noted that the components and raw materials used in the various embodiments and comparative examples of the present invention are commercially available raw materials unless otherwise specified, and the components and raw materials used in each parallel experiment are all of the same kind. The molar parts or weight parts of the components used in the various embodiments and comparative examples of the present invention are only the molar parts or weight parts in a specific embodiment, and can be enlarged or reduced year-on-year in actual production or experiments. The preparation method used in the various embodiments and comparative examples of the present invention is only a preparation method in a specific embodiment, and the operation steps can be appropriately adjusted according to the different production devices or experimental devices in actual production or experiments.
[0031] Examples and Comparative Examples An aging-resistant EVA supercritical foaming sole, the preparation method of which comprises the following steps: S1. Premixing EVA, elastomer, SEBS, crosslinking agent, filler and wear agent in a high mixer to obtain an EVA composition; S2. The composition obtained in S1 is granulated, and then injection molded at an injection temperature of 100°C and a mold temperature of 180°C, and the pressure is maintained for 500s to form a shoe embryo; S3. Place the shoe base obtained in step 2 into N 2 The foaming was carried out in a supercritical reactor, and the N 2 The pressure is 12MPa, the foaming temperature is 150℃, the heat preservation and pressure holding time is 1.5h, then the pressure is released, and the finished sole is obtained after being taken out and cooled to room temperature. The specific components and parts of the EVA supercritical foaming sole are shown in Table 1; Table 1 Specific components and quantities of EVA supercritical foaming soles
[0032] The following performance tests were performed on the EVA supercritical foaming sole, and the results are shown in Table 2: (1) Hardness: The hardness of the examples and comparative examples was tested according to the standard HG / T 2489-2007 “Test method for hardness of microporous materials for footwear”; (2) Impact rebound: The impact rebound performance of the examples and comparative examples was tested with reference to the standard GB / T 1681-2009 “Determination of the resilience of vulcanized rubber”; (3) DIN wear: The wear resistance of the examples and comparative examples was tested with reference to ASTM D1044-19 "Standard test method for abrasion resistance of transparent plastic film surfaces"; (4) Elongation at break: The elongation at break of the examples and comparative examples was tested with reference to the standard GB / T 528-2009 “Determination of tensile stress-strain properties of vulcanized rubber or thermoplastic rubber”; (5) Aging resistance: A damp heat aging test was carried out in a damp heat aging chamber with reference to the standard GB / T 3903.7-2019 "Footwear Test Methods - Aging Treatment" at a temperature of 70±2°C, a relative humidity of 100%, and an aging time of 168 hours. The impact resilience and elongation at break of the embodiments and comparative examples after aging were tested.
[0033] Table 2 Performance test results of EVA supercritical foaming soles
[0034] It can be seen from the test results of the embodiments and the comparative examples that the EVA supercritical foamed sole of the embodiments has significantly improved impact resilience performance, elongation at break, and impact resilience performance and elongation at break after aging, compared with the EVA supercritical foamed sole of the comparative example using a blend of styrene-butyl acrylate-styrene and styrene-ethylene / butylene-styrene block copolymer (SEBS), thereby solving the problem that the existing elastomeric materials cannot have both aging resistance and high resilience.
[0035] As can be seen from Examples 3 to 5, the resilience and aging resistance of the elastomer soft segment with isooctyl acrylate and butyl acrylate as monomers are slightly better than the resilience and aging resistance when ethyl acrylate is used as monomer. As can be seen from Examples 3, 6 to 8, when the molecular weight of the elastomer is between 200,000 and 500,000, the rebound effect of the EVA supercritical foaming sole is the best. When the molecular weight is low, the mechanical properties and rebound performance provided by the elastomer are relatively limited, and when the molecular weight is too high, the elastomer has poor fluidity, which brings difficulties to processing, thereby affecting the mechanical properties of the EVA foam material. As can be seen from Examples 3, 9, and 10, when the content of styrene in the elastomer is increased, its aging resistance becomes better, but the rebound performance will decrease. As can be seen from Example 11, when the proportion of acrylamide in the elastomer is reduced, the rebound performance will significantly decrease due to the decrease in the number of hydrogen bonds. When the elastomer of Comparative Example 1 is not added with acrylamide, the viscosity of the elastomer is large, and there is almost no rebound performance at room temperature, but the elongation at break is good.
[0036] The preferred embodiments of the present invention disclosed above are only used to help illustrate the present invention. The preferred embodiments do not describe all the details in detail, nor do they limit the invention to the specific implementation methods described. Obviously, many modifications and changes can be made according to the content of this specification. This specification selects and specifically describes these embodiments in order to better explain the principles and practical applications of the present invention, so that those skilled in the art can understand and use the present invention well. The present invention is limited only by the claims and their full scope and equivalents.
Claims
1. An aging-resistant EVA supercritical foaming sole, characterized in that: The composition comprises the following components by weight: 10-80 parts of EVA, 10-30 parts of elastomer, 0-20 parts of SEBS, 0-20 parts of filler, 0-10 parts of anti-wear agent, and 0.5-3 parts of cross-linking agent; the elastomer is a block copolymer with polystyrene as a hard segment and acrylate-acrylamide random copolymer as a soft segment, and the general structural formula of the elastomer is shown in Formula 1: Formula 1 Wherein, R is at least one of ethyl, propyl, butyl and isooctyl.
2. The anti-aging EVA supercritical foaming sole according to claim 1, characterized in that: The elastomer contains 10-30 wt % styrene, 50-80 wt % acrylate and 5-20 wt % acrylamide.
3. The anti-aging EVA supercritical foaming sole according to claim 1, characterized in that: The molecular weight of the elastomer is 90,000 to 1,000,000.
4. The anti-aging EVA supercritical foaming sole according to claim 1, characterized in that: Calculated by weight, it includes the following components: 40-80 parts of EVA, 20-30 parts of elastomer, 10-20 parts of SEBS, 10-20 parts of filler, 5-10 parts of wear-resistant agent, and 1-2 parts of cross-linking agent.
5. The anti-aging EVA supercritical foaming sole according to claim 1, characterized in that: The filler is at least one of calcium carbonate, talc, barium sulfate or titanium dioxide.
6. The anti-aging EVA supercritical foaming sole according to claim 1, characterized in that: The anti-wear agent is polysiloxane.
7. The anti-aging EVA supercritical foaming sole according to claim 1, characterized in that: The crosslinking agent is at least one of dicumyl peroxide, di-tert-butyl peroxycumene, 2,5-dimethyl-2,5-bis(tert-butyl peroxide)hexane and tert-amyl peroxy(2-ethylhexyl)carbonate.
8. The anti-aging EVA supercritical foaming sole according to claim 1, characterized in that: The VA content of the EVA is 10wt% to 60wt%.
9. The method for preparing the aging-resistant EVA supercritical foaming sole according to any one of claims 1 to 8, characterized in that: The following steps are involved: S1. Premixing EVA, elastomer, SEBS, crosslinking agent, filler and wear agent in a high mixer to obtain an EVA composition; S2. The composition obtained in S1 is granulated, and then injection molded at an injection temperature of 80 to 130°C and a mold temperature of 150 to 200°C, and the pressure is maintained for 200 to 800s to form a shoe embryo; S3. Place the shoe blank obtained in step 2 into a N2 supercritical reactor for foaming, control the N2 pressure at 10-20 MPa, the foaming temperature at 100-200°C, release the pressure after keeping the temperature and pressure for 0.5-4 hours, take out and cool to room temperature to obtain a finished sole.
10. A sports shoe, characterized in that: The invention comprises the anti-aging EVA supercritical foaming sole as described in any one of claims 1 to 8.